Improving Degree of Comparison Learning Outcomes with Think Pair Share (Education Journal : Journal Educational Research and Development, 2023)
The research aims to find out the results of applying the Think Pair Share (TPS) learning model in improving learning outcomes in English Subjects in the Degree Of Comparison material for class students in class X APHP 3 at SMK N 1 Cangkringan. The approach to this research is a classroom action research approach. The subjects of this study were 34 students of class X APHP 3 at SMKN 1 Cangkringan. The research procedure was divided into two cycles, each cycle consisting of 2 meetings. Data collection techniques used are questionnaires, observation, documentation and tests. The data analysis technique used in this research is quantitative descriptive analysis. Based on the results of the classroom action research conducted by the researcher in two cycles, it was found that there was an increase in English learning achievement in the degree of comparison material in class X APHP 3 at SMK Negeri 1 Cangkringan by 88%.